PERANCANGAN APLIKASI MULTIMEDIA UNTUK PENCEGAHAN COVID-19 PADA ANAK USIA DINI BERBASIS ANDROID - Nur mustika; Kamaruddin Kamaruddin (LPPM Poltek ST Paul, 2021)
Covid-19 disease is a deadly disease caused by the severe acute respiratory virus. This disease attacks all ages, namely the elderly, adolescents, and even early childhood. Efforts to avoid this disease by following health protocols. The purpose of this study is to provide education to early childhood for the prevention of covid-19 disease. The problem faced is the number of protocol rules for handling this disease so that children can apply it in everyday life. The method used in this research is the multimedia development life cycle (MDLC) method. The solution of this research is to design multimedia applications to make it easier to provide education to children by means of images, videos, texts and sounds that can be applied through Android-based applications.